PERENCANAAN KOLAM RETENSI UNTUK PENGENDALIAN BANJIR DI RSMH KOTA PALEMBANG - Alia, Febrinasti; Rhaptyalyani, Rhaptyalyani; Ilmiaty, Reini Silvia (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
Mohammad Hoesin general hospital (RSMH) is a public hospital owned by the Government of Palembang located at Jl. Sudirman . It is located in a densely populated area with total built area of ± 20 ha. The absence of adequate infiltration area plus improper drainage condition and capacity caused floods as high as ± 30 cm in the parking lot which is at the lowest elevation. In order to overcome these problems, RSMH took the initiative to build a retention pond. This study aims to analyze the feasibility of retention pond development plan along with its drainage network through the duflow modeling studio (DMS) approach and spatial analysis of Geographic Information System (GIS). Total catchment for the study area covers the area of ± 46 Ha with the maximum runoff discharge obtained from the modeling results Q = 0,2 m3/s while the waste water effluent that is discharged into the drainage channel Q = 0,0021 m3/s is not too significant therefore can be ignored. Capacity of retention pond with minimum area of 0,7 Ha is sufficient to serve the catchment area, but it should be considered the use of pumps with a capacity of at least 150 lt/s to overcome high elevation difference.